2020
DOI: 10.1002/ppp.2028
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of heat–water–mechanics process in a freezing soil under stepwise freezing

Abstract: Frost heave is a process coupling heat transfer, water migration, water–ice phase change and deformation. Frost heave forms various landforms, such as frost mounds, ice pitons, sorted polygons and stone circles, and potentially induces a variety of engineering failures, such as building inclination, differential engineering foundation and pavement cracking. To understand the mechanism of frost heave under complex freezing paths, we provide a numerical heat–water–mechanics model that incorporates shrinkage in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The initial water content is approximately 25%, and significant water distribution occurred after freezing (Figure 6). The maximum water content related to the formation and growth of the thickest (warmest) ice lens was observed near the freezing front [32]. Furthermore, the discrete ice lenses were discontinuously distributed, and the oscillation of water was ultimately observed in the frozen zone since the newly emerged ice lens can block the water flow to the previously growing ice lens until the warmest ice lens formed (external water can migrate into the frozen fringe and feed the growth of the warmest ice lens).…”
Section: Distribution Of Water Contentmentioning
confidence: 99%
“…The initial water content is approximately 25%, and significant water distribution occurred after freezing (Figure 6). The maximum water content related to the formation and growth of the thickest (warmest) ice lens was observed near the freezing front [32]. Furthermore, the discrete ice lenses were discontinuously distributed, and the oscillation of water was ultimately observed in the frozen zone since the newly emerged ice lens can block the water flow to the previously growing ice lens until the warmest ice lens formed (external water can migrate into the frozen fringe and feed the growth of the warmest ice lens).…”
Section: Distribution Of Water Contentmentioning
confidence: 99%
“…Research on the mechanism of complex frost heave path has been rarely reported before 2019. Bai et al [58] studied the role of frost heave path in the frost heave mechanism based on the existing observations of ice lens distribution and the corresponding numerical simulation (fitting degree = 0:2655 ). They further proposed the three-dimensional THM coupling model with the presence of segregated ice.…”
Section: Development Of Thm Coupling For the Frozen Soilmentioning
confidence: 99%
“…The most utilized journal is Cold Regions Science and Technology that published 103 papers on UWFS, followed by Permafrost and Periglacial Processes and Water Resources Research (Figure 4). The study of frozen soil and unfrozen water is of great significance in engineering [68,69], mechanics [70,71], and water resources or hydrology [72,73] in cold regions. It is understandable that these three journals carried a significantly higher volume of such studies compared to other journals.…”
Section: The Most Recognized Journalsmentioning
confidence: 99%